Cybersecurity in Pakistan: Regulations, Gaps and Way Forward - Khan, Umair Pervez; Anwar, Muhammad Waqar (Massey University)
We live in the age of information and globalization. From paying online utility bills to advance health structure, up to date transportation, use of artificial intelligence, developed communication system and technical warfare, modern states are in continuous progress. Technology has reduced the distances, yet new threats and fears have emerged due to its usage. The digital world is under constant cyber threats and crimes such as hacking, bank frauds, money laundering, information theft, state secrets acquired, and even threats to critical infrastructure have become the evolving trends in cyber warfare. Both the developed states as well as developing nations are exposed to such threats leading to national security dilemma. However, developing country, having nuclear capabilities, like Pakistan, is more vulnerable to these threats. Pakistan also has large number of internet users with low information technology knowledge, thus making it further complex for the government and law-making authorities to regulate its digital world. Recently, Pakistan has faced serious cyber-attacks on important institutional websites and hackers have been able to successfully penetrate the cyber space of important installations. To prevent this from happening, legislators in Pakistan have introduced the cyber laws, which do not seem to cover the threats in depth and totality. This research paper focuses on the cybersecurity framework present in Pakistan while what are the policy options for the state of Pakistan to deal with serious cybersecurity issues is the actual matter of concern? The research methodology is qualitative in nature and researchers have used primary as well as secondary sources to draw the conclusions. At the end, few recommendations regarding the improvement in cyber protocols of the country are also put forth.